The sequence of the 5S ribosomal RNA of the crustacean Artemia salina - Diels, Ludo (1981)
The primary structure of the 5 S rRNA isolated from the cryptobiotic cysts of the brine shrimp Artemia salina is pACCAACGGCCAUACCACGUUGAAAGUACCCAGUCUCGUCAGAUCCUGGAAGUCACACAACGUCGGGCCCGGUCAGUACUUGGAUGGGUGACCGCCUGGGAACACCGGGUGCUGUUGGCAU (OH).